An Organizational Model and Growth of a Free-Standing Physical Therapy Student-Run Clinic - Rayson, Nicole; Weiss, Shelby; Bellizio, Jonathan (Journal of Student-Run Clinics, 2016)
Student-run medical free clinics are becoming a way for students to engage and serve their local communities while improving and growing their own professional skills. Widener University has become one of these institutions of higher education in which their professional programs have embraced service-learning and community engagement into their curriculum. The Institute for Physical Therapy Education at Widener University has added to the institution’s civil mission by opening the Chester Community Physical Therapy Clinic on September 15, 2009. The clinic is completely student-run and follows an organizational model that implements a student board, which with the help of faculty, oversees the daily function of the clinic. Over the last six years, the student board has striven to develop the organizational model to provide the most competent, professional, and consistent care to the clinic’s clients. We hope that this descriptive article can serve as a guide for others who wish to begin or improve upon their own student-run clinics that serve their respective communities.